Penguatan Pembangunan Pertanian sebagai Landasan Pembangunan Perekonomian Indonesia - Simanjutak, Payaman (Unisia, 2016)
The agricultural sector remains playing an important role in the Indonesian economy, in terms of contributing to Gross National Product and to employment generation. In year 2000, agricultural sector contributed 16.7% of the GDP and absorbed 45.3% of the labour force. However, Indonesia has not been able to develop agricultural sector to be self-sufficient for agricultural products. Indonesia is still dependent on import of rice, several kinds of fruits, meats and others. The other problem that Indonesia is facing today and in the future is that almost half of the farmers own less than 0.5 Ha of land, from which they hardly to have decent income. Therefore, the development of agro industries and household businesses is crucially important in order to increase the value of the agricultural products, to stimulate exports of the agricultural products, and to increase the households income.